HS-RAID2: Optimizing Small Write Performance in HS-RAID - Yongfeng Dong; Jingyu Liu; Jie Yan; Hongpu Liu; Youxi Wu (Journal of Electrical and Computer Engineering)
HS-RAID (Hybrid Semi-RAID), a power-aware RAID, saves energy by grouping disks in the array. All of the write operations in HS-RAID are small write which degrade the storage system’s performance severely. In this paper, we propose a redundancy algorithm, data incremental parity algorithm (DIP), which employs HS-RAID to minimize the write penalty and improves the performance and reliability of the storage systems. The experimental results show that HS-RAID2 (HS-RAID with DIP) is faster and has higher reliability than HS-RAID remarkably.